Residents’ Perceptions and Outcomes of Community-Based Tourism in Andro Village of Manipur - Thokchom Ursa; Moirangthem Cha Arunkumar (Dera Natung Government College Research Journal)
Community-based Tourism (CBT) has various impacts on local communities in terms of socio-economic conditions, cultural heritage, environmental safeguards, and overall sustainable development of tourism in the long run. Sustainable development in tourism can be achieved through the independence of local communities and their active participation in tourism activities. Aiming to examine if there is any role of CBT in reaching sustainable goals for tourism, a case study that focuses on the social, economic, environmental and quality of life of the local community of Andro village in Manipur has been taken for study.